COMMUNICATION MEDIATES THE EFFECT OF WORK MOTIVATION AND WORK STRESS ON EMPLOYEE PERFORMANCE - Rio Mattajang (Jurnal Ekonomi, 2022)
This study intends to examine the effect of work motivation and work stress on employee performance through communication as an intervening variable at PT BPRS Baiturridha Pusaka. This research was conducted on 30 employees at PT BPRS Baiturridha Pusaka with data collection techniques in the form of distributing questionnaires. The information collected will be analyzed using the SEM-PLS method using the Smart PLS Version 3.0 program for windows. The results showed that work motivation and communication had a positive effect on employee performance at PT BPRS Baiturridha Pusaka, while work stress had no effect on employee performance and had a positive effect on employee performance at PT BPRS Baiturridha Pusaka. Work motivation on employee performance with communication as an intervening variable has a positive influence on employees at PT BPRS Baiturridha Pusaka. Meanwhile, work stress with communication as an intervening variable has no effect on employees at PT BPRS Baiturridha Pusaka.